Unsupervised use of Gadgets as a Cause of Cyberbullying Among Primary Schoolchildren - Tetyana Blyznyuk (Vasyl Stefanyk Precarpathian National University, 2020)
The article substantiates the relevance of the problem and the consequences of the popularity of modern gadgets (smartphones, laptops, smart TVs, game consoles, health trackers, smart watches, webcams, iPads and tablets, earphones) among primary school students during and beyond the educational process. The author lists the advantages of using innovative digital technologies in the classroom for both the student and the teacher: considerable interest and motivation for learning activities, better opportunities for implementation of the individual learning principle, formation and improvement of necessary life skills and competences, etc. The author presents the results of a survey conducted with HEI academic staff regarding their attitude to the problem and their awareness of the most effective gadgets for the enhancement of educational process. The study also proves the failings of the uncontrolled use of modern technologies among younger students, which has apparently become one of the major reasons for the spread of cyberbullying and aggression in the school environment. The purpose of this paper is to draw attention to this issue and to suggest some ways of addressing it in four stages: family and friends, school, local community and regional-national level, characterized by specific procedures and actions. Among the results of the study, there is an increase in the number of scientific publications, both domestic and foreign, which shows the considerable interest among scientists and the urgent need in the context of searching ways of preventing and combatting cyberbullying among primary school students.